Designing Cutting Tools for The Eva Foam Cutting Process in The Production of Polynet Mesh Spare Parts in CV. ELM Using the QFD Method - Labibah Isnaini Choeronissa; Marina Yustiana Lubis; Yunita Nugrahaini (Institute of Computer Science (IOCS), 2022)
CV. Era Langgeng Mandiri is a company engaged in fabrication and mechanics that implements a make-to-order production strategy. In the production of sparepart mesh polynet, defective products exceed the specified tolerance limit of 5%. Based on the data, defective products often occur during eva foam cutting. We were finding the root cause of the eva foam cutting process using the Six Sigma method with the DMAI approach (Define, Measure, Analyze, Improve). The analysis using fishbone diagrams and 5 why's, found that the factor causing defect products is that the eva foam did not match the pattern. From the root of the problem, the improvement priority was selected using the FMEA, and the highest RPN was 327 in the machine factor. The design that can be done for the root of the problem on the machine factor is the design of the eva foam cutting tool. The design is carried out using the Quality Function Deployment method. The design of the proposed eva foam cutting tool is expected to minimize defect products in the eva foam cutting process as much as 80% of the number of previous defect products and increase process capability by measuring the current sigma level from 3,386 sigma to 3,593 sigma.